Bacterial Endophyte Community Dynamics in Apple (Malus domestica Borkh.) Germplasm and Their Evaluation for Scab Management Strategies - Shahid A. Padder (MDPI AG, 2021)
The large genetic evolution due to the sexual reproduction-mediated gene assortments and propensities has made Venturia inaequalis (causing apple scab) unique with respect to its management strategies. The resistance in apple germplasm against the scab, being controlled for by more than fifteen genes, has limited gene alteration-based investigations. Therefore, a biological approach of bacterial endophyte community dynamics was envisioned across the apple germplasm in context to the fungistatic behavior against V. inaequalis. A total of 155 colonies of bacterial endophytes were isolated from various plant parts of the apple, comprising 19 varieties, and after screening for antifungal behavior followed by morphological, ARDRA, and sequence analysis, a total of 71 isolates were selected for this study. The alpha diversity indices were seen to fluctuate greatly among the isolation samples in context to microflora with antifungal behavior. As all the isolates were screened for the presence of various metabolites and some relevant genes that directly or indirectly influence the fungistatic behavior of the isolated microflora, a huge variation among the isolated microflora was observed. The outstanding isolates showing highest percentage growth inhibition of V. inaequalis were exploited to raise a bio-formulation, which was tested against the scab prevalence in eight apple varieties under controlled growth conditions. The formulation at all the concentrations caused considerable reductions in both the disease severity and disease incidence in all the tested apple varieties. Red Delicious being most important cultivar of the northwestern Himalayas was further investigated for its biochemical behavior in formulation and the investigation revealed different levels of enzyme production, chlorophyll, and sugars against the non-inoculated control.